Robotic Systems on the Frontline Against the Pandemic - Avgousti, Sotiris; Christoforou, Eftychios G.; Masouras, Panicos; Panayides, Andreas S.; Tsekos, Nikolaos V. (My University, 2022)
Robotic systems have been effectively used in healthcare while a new role for them has emerged during the COVID-19 pandemic. Robots were used as part of prevention, screening and diagnosis of the disease, but also to assist with the treatment of patients. The purpose of the paper is to provide an overview of the relevant applications for robots and highlight their potential.
Keywords: Sterilization/Disinfection robots; Nursing robots; Service robotics